Mediaeval Antiquity - Welkenhuysen, Andries (eds) (Mediaevalia Lovaniensia - Series 1/Studia, 1995)
The contributions here assembled originate from papers read to the colloquium on Mediaeval Antiquity which was organized, from 28 to 30 May 1990, by the 'Instituut voor Middeleeuwse studies' at KU Leuven.